Skin Quality – A Holistic 360° View: Consensus Results - Goldie K; Kerscher M; Fabi SG; Hirano C; Landau M; Lim TS; Woolery-Lloyd H; Mariwalla K; Park JY; Yutskovskaya Y (Dove Medical Press, 2021)
Kate Goldie,1,* Martina Kerscher,2,* Sabrina Guillen Fabi,3 Cyro Hirano,4 Marina Landau,5 Ting Song Lim,6 Heather Woolery-Lloyd,7 Kavita Mariwalla,8 Je-Young Park,9 Yana Yutskovskaya10 1European Medical Aesthetics Ltd, London, UK; 2Division of Cosmetic Science, Department of Biochemistry and Molecular Biology, University of Hamburg, Hamburg, Germany; 3Department of Dermatology, University of California, San Diego, CA, USA; 4Division of Dermatology General Polyclinic of Rio de Janeiro, Private Practice, CD Clinica Dermatologica, Rio de Janeiro, Brazil; 5Dermatology Unit, Wolfson Medical Center, Holon, Israel; 6Clique Clinic, Kuala Lumpur, Malaysia; 7Department of Ethnic Skin Care, University of Miami Cosmetic Medicine and Research Institute, Miami Beach, FL, USA; 8Mariwalla Dermatology, New York, NY, USA; 9Apkoo-Jung Department, Oracle Dermatology Center, Seoul, Republic of Korea; 10Dermatovenerology and Cosmetology Department, Pacific State Medical University of Health, Moscow, Russia*These authors contributed equally to this workCorrespondence: Martina KerscherDivision of Cosmetic Science, Department of Biochemistry and Molecular Biology, University of Hamburg, Hamburg, GermanyEmail martina.kerscher@uni-hamburg.deIntroduction: Skin quality is an important component of human attractiveness. To date, there are no standardized criteria for good skin quality. To establish a consensus for good skin quality parameters and measurement and treatment options, a virtual skin quality advisory board consisting of a global panel of highly experienced aesthetic dermatologists/aesthetic physicians was convened.Methods: A total of 10 dermatologists/aesthetic physicians served on the advisory board. A modified version of the Delphi method was used to arrive at consensus. Members accessed an online platform to review statements on skin quality criteria from their peers, including treatment and measurement options, and voted to indicate whether they agreed or disagreed. Statements that did not have agreement were modified and the members voted again. Consensus was defined as: strong consensus = greater than 95% agreement; consensus = 75% to 95% agreement; majority consent = 50% to 75% agreement; no consensus = less than 50% agreement.Results: There was strong consensus that good skin quality is defined as healthy, youthful in appearance (appearing younger than a person’s chronological age), undamaged skin and that skin quality can be described across all ethnicities by four emergent perceptual categories (EPCs): skin tone evenness, skin surface evenness, skin firmness, and skin glow. The EPCs can be affected by multiple tissue layers (ie, skin surface quality can stem from and be impacted by deep structures or tissues). This means that topical approaches may not be sufficient. Instead, improving skin quality EPCs can require a multilayer treatment strategy.Conclusion: This global advisory board established strong consensus that skin quality can be described by four EPCs, which can help clinicians determine the appropriate treatment option(s) and the tissue or skin layer(s) to address. Skin quality is important to human health and wellbeing and patients’ perception for the need for aesthetic treatment.Keywords: aesthetic treatment, consensus, emergent perceptual skin quality categories, EPCs, skin quality